Controlling pyridinic, pyrrolic, graphitic, and molecular nitrogen in multi-wall carbon nanotubes using precursors with different N/C ratios in aerosol assisted chemical vapor deposition. Issue 37 (7th October 2015) - Bulusheva, L. G.; Okotrub, A. V.; Fedoseeva, Yu. V.; Kurenya, A. G.; Asanov, I. P.; Vilkov, O. Y.; Koós, A. A.; Grobert, N.
<x xml:space="preserve">Abstract</x> The change in the N/C ratio in feedstock allows controlling nitrogen species incorporation into multi-wall carbon nanotubes during CCVD.